A predictive scoring system for proximal junctional kyphosis after posterior internal fixation in elderly patients with chronic osteoporotic vertebral fracture: A single-center diagnostic study - Du, Xing; Jiang, Guanyin; Zhu, Yong; Luo, Wei; Ou, Yunsheng (Frontiers in Endocrinology, 2022)
Objective To establish a predictive scoring system for proximal junctional kyphosis (PJK) after posterior internal fixation in elderly patients with chronic osteoporotic vertebral fracture (COVF). Materials and methods The medical records of 88 patients who were diagnosed with COVF and underwent posterior internal fixation in our hospital from January 2013 to December 2017 were retrospectively analyzed. The included patients were divided into two groups according to whether they suffered PJK after surgery, namely, the PJK group (25 cases) and the non-PJK group (63 cases). The following clinical characteristics were recorded and analyzed: age, gender, body mass index (BMI), bone mineral density (BMD), smoking history, fracture segment, proximal junction angle (PJA), sagittal vertebral axis (SVA), pelvic incidence (PI) - lumbar lordosis (LL), pelvic tilt (PT), sacral slope (SS), posterior ligamentous complex (PLC) injury, upper instrumented vertebra (UIV), lower instrumented vertebra (LIV) , and number of fixed segments. The prevalence of these clinical characteristics in the PJK group was evaluated, and the scoring system was established using logistic regression analysis. The performance of the scoring system was also prospectively validated. Results The predictive scoring system was established based on five clinical characteristics confirmed as significant predictors of PJK, namely, age > 70 years, BMI > 28 Kg/m2, BMD < -3.5 SD, preoperative PI-LL > 20°, and PLC injury. PJK showed a significantly higher score than non-PJK (7.80 points vs. 2.83 points, t=9.556, P<0.001), and the optimal cut-off value for the scoring system was 5 points. The sensitivity and specificity of the scoring system for predicting postoperative PJK were 80.00% and 88.89%, respectively, in the derivation set and 75.00% and 80.00% in the validation set. Conclusion The predictive scoring system was confirmed with satisfactory sensitivity and specificity in predicting PJK after posterior internal fixation in elderly COVF patients. The risk of postoperative PJK in patients with a score of 6 to 11 is high, while the score of 0 to 5 is low.